(untitled) (American Journal of Business Management, Economics and Banking, 2023)
With the change of the currency regime rate from crawling peg to almost floating regime Uzbekistan government is trying to remove all restrictions regarding foreign currency use by individuals as well as companies and liberalize its currency regulations. On the one hand this long-awaited reform which allowed everyone equal access to currency markets, gives local businesses and individual opportunities to employ foreign currency operations, but on the other hand it will make the national currency exchange rate extremely volatile and have a big impact on companies with assets and liabilities denominated in foreign currencies making them exposed to foreign exchange risk. The paper will investigate the condition of the exchange risk management in Uzbek financial organizations and try to identify problems and challenges related to currency risk management methods and techniques. Moreover, level of currency risk exposure and tools used by the commercial banks for risk management will be reviewed. Experience of the World Bank, Asian Development Bank, European Bank of Reconstruction and Development, International Monetary Fund and Japanese banks will be reviewed and discussed.